UTILIZATION OF TREATED SEWAGE WASTEWATER FOR GREEN FORAGE PRODUCTION INA HYDROPONIC SYSTEM - Al-Karaki, Ghazi . N (Emirates Journal of Food and Agriculture, 2011)
Using alternative water resources such as tertiary treated sewage wastewater is considered very important to produce crops (e.g., green forage) due to irrigation water shortage, especially in arid and semiarid regions like Jordan. Moreover, growing forage hydroponically is now becoming popular in drought prone areas to produce green fodders in large quantities with less water use. The objectives of this study were to investigate the effects of irrigation with tertiary sewage treated wastewater (WW), tap water (TW) or mixed WW with tap water (WW mix) on barley (Hordeum vulgare L.) fodder yield, quality, and water use efficiency (WUE) under hydroponic conditions. A hydroponic system was developed with four shelves and used in this study. The results showed that barley forage can be produced in 9 days from planting to harvest in this system. Using WW in irrigation has effectively increased the yields of green and dry fodder, and the green forage yields obtained were 224, 276 and 320 tons/ha under irrigation with TW, WW mix and WW, respectively. The higher fodder yields obtained with WW than TW or WW mix, probably due to the higher nutritive value of WW especially N content. However, plants irrigated with WW used water more efficiently than those irrigated with other water types, when used 1.26 m3 compared to 1.56 m3 water in TW to produce 1 ton of hydroponic green fodder. Proximate and mineral nutrient contents of dry fodder were significantly higher in plants irrigated with WW than with TW in respect to crude protein, acid and neutral detergent fiber, and N, K, Mg, and Na contents. Heavy metal (Cd, Pb, and Ni) contents in barley fodder were higher in plants irrigated with WW than those irrigated with TW, but their levels did not reached the maximum allowed levels by FAO for edible crops. The results of this study revealed that hydroponic green barley fodder could be irrigated safely with tertiary treated sewage wastewater to produce high yields and less water use. Moreover, use of treated wastewater in irrigation of green forages in hydroponic system considered as useful alternative disposal method of wastewater without the risk of accumulation of heavy metals in the soil.